2014
DOI: 10.1185/03007995.2014.975339
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Japanese women with postmenopausal osteoporosis treated with raloxifene and vitamin D: post hoc analysis of a postmarketing study

Abstract: Active vitamin D3 supplementation to raloxifene treatment for 24 weeks may have additional benefits in improving QOL and relieving pain in Japanese women with postmenopausal osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Raloxifene alone for 6 or 12 months was shown to improve EQ-5D in Japanese and European women 12 , 13 . Our results are consistent with a previous study demonstrating that 6-month combination therapy with raloxifene and alfacalcidol significantly improved QOL assessed using EQ-5D compared with baseline or raloxifene alone in 506 Japanese postmenopausal women with osteoporosis 11 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Raloxifene alone for 6 or 12 months was shown to improve EQ-5D in Japanese and European women 12 , 13 . Our results are consistent with a previous study demonstrating that 6-month combination therapy with raloxifene and alfacalcidol significantly improved QOL assessed using EQ-5D compared with baseline or raloxifene alone in 506 Japanese postmenopausal women with osteoporosis 11 .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, a combination treatment containing SERM and vitamin D is expected to improve compliance and convenience as well as the effectiveness of osteoporosis treatment. In addition, beyond bone density and fracture, improvement in quality of life (QOL) is an important outcome in the treatment of osteoporosis 11 . Several studies have investigated the effects of anti-osteoporotic medications such as raloxifene or vitamin D alone on QOL 12 14 , but the effects of SERM and vitamin D combination therapy on QOL have not been fully evaluated 11 .…”
Section: Introductionmentioning
confidence: 99%
“…30 For this reason, RLX is often prescribed in combination with vitamin D. Post hoc analysis of the combination of RLX and vitamin D in Japan demonstrated sufficient drug safety in patients aged ≥75 years with osteoporosis. 20 Also, the combination treatment of RLX and vitamin D was compared with no medication (no RLX group), similar to the actual clinical situation. The results of this study consistently demonstrated that the combination of RLX and vitamin D prevented a decrease in the local BMD and improved rotator cuff tendon-to-bone healing in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…2,11 Raloxifene (RLX) is one of these SERMs, and a combination of RLX and vitamin D is widely used in postmenopausal women. 7,20,24 Few studies, however, have reported on the interaction between estrogen and the rotator cuff enthesis. Recently, an estrogen-deficient state in rats that have undergone ovariectomy (OVX) has been shown to worsen the biomechanical properties of bone-to-tendon healing and inhibit chondroid tissue formation in repair tissue.…”
mentioning
confidence: 99%
“…The therapeutic response of raloxifene varies widely among patients; a few cases of osteonecrosis of the jaw have been reported (Bindakhil et al, 2021). With raloxifene, prospective (Scharla et al, 2006) and post hoc (Ohta et al, 2015) studies showed an improvement of pain. In a RCT (Fujita et al, 2010), back and knee pain were improved with raloxifene, when measured by VRS (p = 0.0017) and electroalgometry (p = 0.0045).…”
Section: Sermsmentioning
confidence: 95%